2017
DOI: 10.1021/acs.langmuir.7b00170
|View full text |Cite
|
Sign up to set email alerts
|

Playing with Emulsion Formulation to Control the Perforation of a Freely Expanding Liquid Sheet

Abstract: A single-drop experiment based on the collision of one drop of liquid on a small solid target is used to produce liquid sheets that are visualized with a fast camera. Upon impact, the drop flattens into a sheet that is bounded by a thicker rim and radially expanding in air. Emulsion-based liquid sheets are destabilized through the nucleation of holes that perforate the sheet during its expansion. The holes grow until they merge together and form a web of ligaments, which are then destabilized into drops. We pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Focusing first on the lower liquid supply pressure series of images (a,c,e), shadowgrams confirm the formation of holes in the oil-emulsion spray fan which do not appear in the single phase water spray fan. This is consistent with prior studies of spray fan breakup in oil-in-water emulsions (Qin et al, 2010;Hilz et al, 2012;Altieri et al, 2014;Vernay et al, 2015;Vernay et al, 2016;Vernay et al, 2017). Increasing the oil volumetric concentration in the emulsion visibly leads to initial hole formation closer to the spray nozzle and an apparent increase in the hole formation rate (number of holes per image).…”
Section: Qualitative Examination Of Spray Breakup Processsupporting
confidence: 91%
See 1 more Smart Citation
“…Focusing first on the lower liquid supply pressure series of images (a,c,e), shadowgrams confirm the formation of holes in the oil-emulsion spray fan which do not appear in the single phase water spray fan. This is consistent with prior studies of spray fan breakup in oil-in-water emulsions (Qin et al, 2010;Hilz et al, 2012;Altieri et al, 2014;Vernay et al, 2015;Vernay et al, 2016;Vernay et al, 2017). Increasing the oil volumetric concentration in the emulsion visibly leads to initial hole formation closer to the spray nozzle and an apparent increase in the hole formation rate (number of holes per image).…”
Section: Qualitative Examination Of Spray Breakup Processsupporting
confidence: 91%
“…However, as higher backing pressure leads to smaller wavelength oscillations in the sheet, holes are more difficult to discern in high pressure spray shadowgrams. Consistent with the depiction provided by Vernay et al (Vernay et al, 2015;Vernay et al, 2017), holes visibly expand as they migrate downstream in the spray fan, and upon merging, they lead to ligament formation in the fan. Ligaments, in turn, break-up into droplets.…”
Section: Qualitative Examination Of Spray Breakup Processsupporting
confidence: 79%
“…Our data and model also rationalize some of the anecdotal and scattered observations on lifetimes, some of which did report an increase in lifetime in saltwater upon decrease of relative humidity (Talmud & Suchowolskaju 1931;Burger & Blanchard 1983) as well as bubbles living for up to several minutes in seawater (Garrett 1967;Gluhosky 1983). It should be noted that while it is clear that salt delays the burst of water bubbles by affecting their drainage, Vernay et al (2017) have reported that films of oil-water salty emulsions are more unstable with salt. In that case, a different bursting mechanism is at play, where the adjunction of salt can promote film bursting rather than preventing it as follows.…”
Section: Analogue Experimentsmentioning
confidence: 99%
“…Furthermore, we sprayed different other adjuvants only at the label dosage. The choice of using only relatively simple soluble surfactants limits the scope of the current investigation; there are of course different spray additives, for example polymer solutions, 17 emulsions, 18 etc., and many other types of sprays and nozzles (air induced nozzles, pre-orifice nozzles, atomizers, etc.) but these are beyond the scope of the present article.…”
Section: Introductionmentioning
confidence: 99%